1995
DOI: 10.1099/0022-1317-76-11-2779
|View full text |Cite
|
Sign up to set email alerts
|

Rinderpest virus infection of bovine peripheral blood monocytes

Abstract: The ability of rinderpest virus (RPV) to replicate in vitro in adherent peripheral blood monocytes and monocytederived macrophages under non-stimulation conditions was investigated. When flow cytometry analysis on bovine peripheral blood mononuclear cells (PBMC) was performed, monocytic cells were seen to be targets for infection by the cell culture-attenuated RBOK vaccine strain of RPV. Viral glycoprotein (H) and nucleoprotein (N) expression in adherent blood monocytes and monocyte-derived macrophages was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Examples of other large-scale epidemics with a wide host range (affecting multiple different species) include chytridiomycosis, caused by Batrachochytrium dendrobatidis , in numerous amphibian species [42], rinderpest in African artiodactyls [43], and West Nile Virus in North American birds [44]. In all three examples, the overall impact has been devastating; however, like we show here, species-specific differences have been reported.…”
Section: Discussionsupporting
confidence: 59%
“…Examples of other large-scale epidemics with a wide host range (affecting multiple different species) include chytridiomycosis, caused by Batrachochytrium dendrobatidis , in numerous amphibian species [42], rinderpest in African artiodactyls [43], and West Nile Virus in North American birds [44]. In all three examples, the overall impact has been devastating; however, like we show here, species-specific differences have been reported.…”
Section: Discussionsupporting
confidence: 59%
“…After infection, Ͻ10% (maximum) of the viable PBMC population were seen to express virus antigen. Phenotypic analysis demonstrated that these were mainly monocytes; as previously reported (20), the majority of these CD14 ϩ cells supported active replication of RPV. Among lymphocytes, Ͻ2% expressed viral antigen after infection, primarily within the CD8 ϩ T-cell population.…”
Section: Discussionsupporting
confidence: 82%
“…Bovine lymphoblastoid cell lines, transformed with the parasite T. parva, of either Bor T-cell phenotype could also support replication, in this case, that of vaccine strain RPV-RBOK (21). By using this same vaccine strain, we (20) demonstrated that RPV productively infected blood-adherent cells. These were shown clearly to be monocytes and monocyte-derived macrophages by double-labelling experiments using MAbs against the H glycoprotein of RPV and the CD14 marker characteristically found on monocytic cells.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The host range of RPV includes domestic cattle, water buffalo, sheep, goats, and pigs (28). In cattle, target cells for RPV are epithelial cells, activated lymphocytes, and macrophages (34,37,49). Virus isolation is carried out routinely in primary bovine kidney cell cultures or a Theileria parva-transformed bovine lymphocyte cell line (38).…”
mentioning
confidence: 99%